Application of the scaled-opposite-spin approximation to algebraic diagrammatic construction schemes of second order - Krauter, Caroline M.; Pernpointner, Markus; Dreuw, Andreas (The journal of chemical physics, 2013)
With the concept of scaled-opposite-spin (SOS), a pragmatic semi-empirical approximation has been introduced to the extended algebraic diagrammatic construction scheme of second order (ADC(2)-x) that leads to a significant saving in computational effort. The parameters included were fitted with respect to a benchmark set of electronically excited states in standard organic molecules that include some doubly-excited states, as well.
Gesehen am 15.12.2017